Seropidemiological study of Chlamydia trachomatis infections in blood donors from the Santa Casa de Misericórdia de Porto Alegre, Rio Grande do Sul, Brazil - Lessa Filho, José dos Santos (Revista de Ciências Médicas e Biológicas, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> The prevalence of antibodies to Chlamydia trachomatis and epidemiological factors associate with the chlamydial infection were studied in donors of a blood bank located in Porto Alegre – RS/Brazil. In a total number of 494 blood samples, 149 (30.2%) were positive for C. trachomatis, 105 (28.2%) from males and 44 (36.4%) from females. The higher risk to acquire chlamydial infections was observed in 28-32-year old females with past clinical history of amniotic sac rupture and premature newborn as well as 23-27-year old males with past clinical history of gonorrhea and/or other sexually transmitted diseases (STDs).